Cage-confinement pyrolysis route to size-controlled molybdenum-based oxygen electrode catalysts: From isolated atoms to clusters and nanoparticles. (January 2020) - Kou, Zongkui; Zang, Wenjie; Ma, Yuanyuan; Pan, Zhenghui; Mu, Shichun; Gao, Xiaorui; Tang, Baoshan; Xiong, Mo; Zhao, Xiujian; Cheetham, Anthony K.; Zheng, Lirong; Wang, John
Abstract: Metal-nitrogen-carbon materials with properly tailored metal particle sizes offer an ideal model system for electrocatalysis due to their readily tunable dimension, geometric and electronic effects at the catalytically active sites. Herein, a cage-confinement pyrolysis route is proposed to realize size-controllable synthesis of molybdenum-based catalysts ranging from isolated single Mo atoms to sub-nanometer clusters (<1 nm) and nanoparticles (2–5 nm). The effective control in the degree of dispersion facilitates a rational investigation into the electrocatalytic behavior of metal species from the angstrom to the nanometer scales. Notably, the Mo single atom catalysts show superior activity for bifunctional oxygen reduction and evolution reactions (ORR/OER) with a smaller potential gap of 0.65 V, which are compared favorably with the analogous sub-nanometer clusters and nanometer-level particles. X-ray fine structure analyses coupled with theoretical calculations demonstrate that the active Mo sites in the Mo1 N1 C2 local coordination environment have promoted the reversible oxygen electrode reactions. As a demonstration of their real application potentials, the zinc-air batteries assembled by using the highly active Mo single atom catalysts as the air cathode deliver a specific capacity of 750 mA h gZn −1 with an energy density of 673 W h kgZn −1, comparable to a mixed Pt/C-RuO2 benchmark. Graphical abstract: Image 1 Highlights: A cage-confinement pyrolysis route is proposed to downsize metal species from nanometer to angstrom. Molybdenum-based nanoparticles, sub-nanometer clusters and single atoms are synthesized. The smallest Mo single atoms exhibit the best ORR/OER activities. DFT calculations confirm that Mo1 N1 C2 configuration is the origin of bifunctional activities. Zn-air battery assembled with Mo single atoms demonstrates the excellent cycling performance.